2011
DOI: 10.1371/journal.pone.0014555
|View full text |Cite|
|
Sign up to set email alerts
|

Serological Evidence of Subclinical Transmission of the 2009 Pandemic H1N1 Influenza Virus Outside of Mexico

Abstract: BackgroundRelying on surveillance of clinical cases limits the ability to understand the full impact and severity of an epidemic, especially when subclinical cases are more likely to be present in the early stages. Little is known of the infection and transmissibility of the 2009 H1N1 pandemic influenza (pH1N1) virus outside of Mexico prior to clinical cases being reported, and of the knowledge pertaining to immunity and incidence of infection during April–June, which is essential for understanding the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
3
16
1
Order By: Relevance
“…Serological analysis provided a picture consistent with what has been reported in other countries: whichever HI threshold was considered, the highest prevalence levels and HI titres were identified in ( i ) individuals under 20 yo, reflecting the fact that this age group was the primary target of the pandemic virus [7], [8], [12], [17][19], [30][38], and ( ii ) the elderly. Elderly individuals were paradoxically poorly impacted by the first wave, most probably because of pre-existing cross-reactive antibodies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Serological analysis provided a picture consistent with what has been reported in other countries: whichever HI threshold was considered, the highest prevalence levels and HI titres were identified in ( i ) individuals under 20 yo, reflecting the fact that this age group was the primary target of the pandemic virus [7], [8], [12], [17][19], [30][38], and ( ii ) the elderly. Elderly individuals were paradoxically poorly impacted by the first wave, most probably because of pre-existing cross-reactive antibodies.…”
Section: Discussionsupporting
confidence: 81%
“…They may have been infected with Spanish flu-related A(H1N1) strains prior to the major antigenic drift of A(H1N1) viruses that occurred at the end of the 1940s [39]. These antibodies had been detected in individuals over 60 yo in most previous sero-epidemiological studies [7], [8], [17], [30], [32], [38], [40][52], with the exception of three studies in China [53], Taiwan [19], and Singapore [54], where none of the participants over 60 yo was seropositive for pandemic 2009 A(H1N1) antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion was also drawn from Australian sequences [44]. A study reported from Taiwan [45] showed evidence of pre-epidemic subclinical community transmission as proved by seroconversion occurring several weeks before report of the first documented case in the island.…”
Section: Discussionsupporting
confidence: 75%
“…It was also lower than that of the winter outbreak in the Southern Hemisphere around the same time [19,32,33], perhaps attributable to the fact that it was the winter influenza season in the Southern Hemisphere. Moreover, It is lower than the final size estimate of R 0 (1.87; 95% CI: 1.68-2.06) obtained from serological study of a cohort household population in central Taiwan during the same period of time [1]. However, we note that this disparity is reasonable since the serologic data used for this estimate accounts for the asymptomatic cases among the cohort group.…”
Section: Discussioncontrasting
confidence: 64%
“…Serological evidence has indicated that approximately one in every ten persons was infected with the 2009 pH1N1 virus in central Taiwan by April-June [1,27]; hence the estimates using data after July does not yield, and can reasonably be expected to be lower than, the more commonly known basic reproduction number R 0 .…”
Section: Discussionmentioning
confidence: 99%